2013
DOI: 10.1007/s40368-013-0046-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the tooth brushing skills in children aged 6–12 years

Abstract: Tooth brushing skills improved with age and the duration of tooth brushing made a significant difference to the oral hygiene status of the child. The type of grip used and gender did not influence tooth brushing ability in this group of children. Tooth brushing skills were low in children younger than 10 years of age. Hence, parental supervision is considered necessary and recommended until 10 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…The observed time spent on toothbrushing, 71 s, is comparable to that observed in previous studies of child tooth brushing 18 but much shorter than recommended 19 . Interestingly, longer durations of independent child toothbrushing were associated with more dmfs and greater likelihood that the child had required general anesthesia for a dental procedure.…”
Section: Discussionsupporting
confidence: 85%
“…The observed time spent on toothbrushing, 71 s, is comparable to that observed in previous studies of child tooth brushing 18 but much shorter than recommended 19 . Interestingly, longer durations of independent child toothbrushing were associated with more dmfs and greater likelihood that the child had required general anesthesia for a dental procedure.…”
Section: Discussionsupporting
confidence: 85%
“…It also very important to apply a proper method since children differ in their abilities of brushing and that is dependent on their experience as well as physical and neurological development [ 16-18 ]. It has been proven that brushing skills get better with age and that the duration of brushing is significant for oral hygiene of children as well [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health educational programs are as an effective tool in children motivation to perform oral hygiene were found by the different authors [ 9 , 13 , 16 , 19 ]. It order to obtain/gain best possible results and have a long term effect, those should include and stimulate collaboration between school personal, medical staff and parents.…”
Section: Discussionmentioning
confidence: 99%
“…Ogasawara reported that it was impossible for children to reach the entire tooth surface until they are 6 years old [14] and Mescher reported that hand function is an age-related factor in subject's tooth brushing ability to perform Bass methods [15]. From this point, many reports recommended that adults perform or supervise oral cleaning for young children, who until approximately 5-10 years of age lack the dexterity and cognition needed for adequate cleaning [15][16][17]. Therefore caregivers'-toothbrushing is an important factor in maintaining children's oral hygiene.…”
Section: Discussionmentioning
confidence: 99%